PENGARUH REPUTASI AUDITOR DAN PROFITABILITAS PERUSAHAAN TERHADAP AUDITOR SWITCHING - Napisah, Lilis Saidah (Accounting Undergraduate (S1) and Diploma Study Program (D3), STIE EKUITAS, 2025)
This purpose of this research is to find out the influence of the auditor reputation and company profitability on auditor switching in property, real estate and building construction companies listed on the Indonesia Stock Exchange in 2014-2018. The sample research method used purposive sampling technic in which according to the specified criteria obtained by 23 companies. The analytical method used in this research is descriptive analysis with hyphotesis using logistic regression models. Data collection was obtained by accessing the website www.idx.co.id in report form annually company on 2014-2018. Based on the result of testing this research shows that (1) auditor reputation partially has a significant negative effect on auditor switching, (2) company profitability is partially significant positive effect on auditor switching, (3) auditor’s reputation and company profitability simultaneously have a significant effect on the Auditor Switching.